2022
DOI: 10.3390/su14148772
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Barriers and Facilitators of Sustainability for Indonesian Batik SMEs: A Policy Agenda

Abstract: The implementation of sustainability-oriented practices in small- and medium-sized enterprises (SMEs) has been discussed frequently over the years. Recent studies on sustainability have focused mainly on links between ecological and economic sustainability. This exploratory study aims to explore institutional barriers and facilitators regarding the implementation of sustainability-oriented practices in the Indonesian batik industry and to provide policy recommendations. The Indonesian batik industry is well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The literature has also extensively investigated institutional barriers to the growth of entrepreneurship (Daneshniya et al 2021;Gunawan et al 2022). Institutional barriers are essential to consider because they can significantly impact the growth and development of entrepreneurship (Hoogendoorn et al 2019).…”
Section: Institutional Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has also extensively investigated institutional barriers to the growth of entrepreneurship (Daneshniya et al 2021;Gunawan et al 2022). Institutional barriers are essential to consider because they can significantly impact the growth and development of entrepreneurship (Hoogendoorn et al 2019).…”
Section: Institutional Barriersmentioning
confidence: 99%
“…These institutional barriers are vital because they can limit the number of individuals who can start and grow successful businesses. This can negatively impact economic growth, job creation, and innovation (Gunawan et al 2022). Addressing these barriers can help create a more supportive environment for entrepreneurs, enabling them to start and grow successful businesses and contribute to the economy (Daneshniya et al 2021).…”
Section: Institutional Barriersmentioning
confidence: 99%
“…Anggadwita et al (2022) revealed that women entrepreneurs have the initiative in dealing with the COVID-19 pandemic to develop and implement resilience in family businesses. In addition, Gunawan et al (2022) revealed that Indonesian women appear to be more willing or able to deal with uncertainty during the pandemic compared to their male counterparts. Women entrepreneurs also have a choice of strategies for maintaining their businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Batik is well known as an art and cultural heritage representing Indonesia's national identity (Gunawan et al ., 2022). In 2009, United Nations Educational, Scientific and Cultural Organization (UNESCO) designated Indonesian Batik as an Intangible Cultural Heritage of Humanity, which further cemented its important position in Indonesian society (UNESCO, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The values in traditional Batik are lifted from the process of cultural acculturation. Batik can be a representative of the emblem of the art region of each region (Gunawan et al, 2022). However, Indonesian Batik has meaning in every motif caused, so it is not a mass product.…”
Section: Introductionmentioning
confidence: 99%